Adverse drug reactions to first line anti-tuberculosis drugs in newly diagnosed tuberculosis patients - Kolanchinathan, Elakkya; Harichandran, Dhanya Thirookaran; Balakrishnan, Sujatha Mangattuvalappil; Balakumaran, Sanal Kumar Kondarappassery (International Journal of Basic & Clinical Pharmacology, 2021)
Tuberculosis (TB) continues to be an important public health problem throughout much of the world. Drug treatment is the only effective treatment method, but adverse drug events (ADEs) and adverse drug reactions (ADRs) can affect medical adherence. As the number of drug resistant TB patients and the number of anti-TB drugs have increased, it is necessary to explore the risk factors for ADEs/ADRs to reduce their occurrence. Here we reported three different cases of ADRs due to first line anti-tubercular drugs.